PENGEMBANGAN INSTRUMEN EVALUASI BERBASIS GAMBAR SEBAGAI ALAT ASESMEN ALTERNATIF PADA PEMBELAJARAN IPAS SISWA KELAS III - Sri Wenni; Eva Betty Simanjuntak; Nurmayani; Suyit Ratno (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2026)
This study develops image-based evaluation instruments as alternative assessments for Grade III IPAS learning on changes in the state of matter, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study was conducted at SDN 101280 Gunungtua Tonga with 20 Grade III students as subjects and three expert validators. Data were collected through expert validation sheets (Aiken V formula), teacher and student response questionnaires, and empirical item analysis. Results show: (1) the instrument is valid, with Aiken V scores of 0.850 (content), 0.875 (design), and 0.900 (evaluation) — all exceeding the minimum threshold of 0.600; 25 of 40 initial items (62.5%) passed selection; all 25 items were empirically valid (r > 0.444); (2) the instrument is very practical with a combined score of 87.32% from teacher (88.33%) and student (86.3%) responses; (3) the instrument is effective, with 100% of multiple-choice distractors functioning, proportional difficulty distribution, and a class average score of 61.1% (Effective category). The instrument is recommended as an alternative IPAS assessment tool in elementary schools.